2017
DOI: 10.2147/amep.s127007
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in residents-as-teachers across graduate medical education

Abstract: BackgroundTeaching residents how to teach is a critical part of residents’ training in graduate medical education (GME). The purpose of this study was to assess the change in resident-as-teacher (RaT) instruction in GME over the past 15 years in the US.MethodsWe used a quantitative and qualitative survey of all program directors (PDs) across specialties. We compared our findings with a previous work from 2000–2001 that studied the same matter. Finally, we qualitatively analyzed PDs’ responses regarding the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 12 publications
2
34
0
3
Order By: Relevance
“…9 In our study, the core specialties of internal medicine, adult neurology, obstetrics and gynecology, pediatrics, adult psychiatry, and general surgery had the highest proportion of respondents who reported current resident-as-teacher programs. This finding is similar to that of a national survey by Achkar et al 15 on the prevalence of resident-as-teacher programs, where the highest proportions of responding programs were in medicine (20.4%), pediatrics (15.4%), and emergency medicine (11.8%). Given the ACGME mandate, it is not surprising that residency core specialties are more likely to report having resident-as-teacher programs.…”
Section: Discussionsupporting
confidence: 89%
“…9 In our study, the core specialties of internal medicine, adult neurology, obstetrics and gynecology, pediatrics, adult psychiatry, and general surgery had the highest proportion of respondents who reported current resident-as-teacher programs. This finding is similar to that of a national survey by Achkar et al 15 on the prevalence of resident-as-teacher programs, where the highest proportions of responding programs were in medicine (20.4%), pediatrics (15.4%), and emergency medicine (11.8%). Given the ACGME mandate, it is not surprising that residency core specialties are more likely to report having resident-as-teacher programs.…”
Section: Discussionsupporting
confidence: 89%
“…Another reason highlighted to stop RaT programs was that they were supposedly undesired. Perceptions such as “they are already aware of teaching students” are not uncommon as this was shared amongst many of our peers 1. However, the consensus amongst students after completing the course was that it highlighted the skill and training required to deliver good medical teaching, which could improve the uptake of future clinical RaT programs.…”
Section: Dear Editormentioning
confidence: 94%
“…We read with great interest the article by Al Achkar et al highlighting the importance of residents-as-teachers (RaT) programs 1. The increasing use of RaT instruction resonated with us from a medical student perspective, as a program that should be adapted and implemented as early as medical school to allow students to develop key teaching skills as well as enhance their own learning.…”
Section: Dear Editormentioning
confidence: 99%
“…87% of pediatric residency program directors in the United States reported having a resident-as-teachers (RAT) curriculum, but only 17% considered the program to be very or extremely effective (Fromme, 2011). In family medicine, one study concluded that 85% of residencies offered a RAT program in 2014, though effectiveness was not measured (Al Achkar, 2017). Clearly, attempts have been made to implement RAT curriculums, at least in some residencies, but as a profession, we should consider making serious improvements.…”
Section: Perspectivementioning
confidence: 99%